PEGASUS-TIMI 54 Subanalysis - Rizzo, Toni (MD Conference Express, 2015)
The PEGASUS-TIMI 54 trial demonstrated that continuing treatment with ticagrelor after 1 year following myocardial infarction protected patients from ischemic events and provided a more robust risk reduction compared to reinitiation in stable patients on aspirin monotherapy. Patients who were treated with only aspirin for > 1year after myocardial infarction did not derive any benefit from reinitiation of P2Y12 inhibitor therapy and had an increased risk of bleeding.